Statistical genetics in forensic science - Curran, James M. (Henry Stewart Talks, 2016)
DNA profiles, Population frequencies, Three principles of interpretation, Odds form of Bayes' theorem, Hardy Weinberg equilibrium, Relatedness, Genetic drift